E-agriculture: developing a decision support system for precision farming - Konstantinou, Loukas (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2018)
This research belongs to the field of Information and Communication Technologies but takes on a cross-disciplinary approach, since it engages the field of agriculture and specifically the farming sector. The purpose of this study is to develop an effective Decision Support System that gathers weather based and agricultural data, formulates them and displays the most prominent results, prompting the user to take the appropriate action. By achieving this goal, this research also contributes to Precision Agriculture and sustainable food production. The overall Decision Support System comprises hardware and software elements and it is broken down into a pair of activities. Each activity consists of two smaller parts for better management. The methodology that was adopted for the purposes of the current study is quantitative, while the method is the experiment. For accomplishing this experiment, particular equipment was employed for gathering the data, a platform was utilized for storing the information and an Android application was developed for formulating and presenting the most crucial results back to the user. Additionally, as far as the outcomes are concerned, the Decision Support System has been fully developed and formed, according to the comprehensive and detailed system design, composition and arrangement of the various components. A complete testing of the system in actual farmlands and with farmers or farming consultants was not possible due to time constraints. Nevertheless, the proposed Decision Support System is available for deployment and usage.
Keywords: Information and Communication Technologies; cross-disciplinary approach